Investigation of Antioxidant, In-vitro Cytotoxic, and In-vivo Antitumor Effects of Leaf Extracts of Annona Reticulata - Biswas, Shashwata; Shahriar, Mohammad; Khanam, Jahan Ara; Ahsan, Chowdhury Rafiqul (Bangladesh Journal of Microbiology, 2016)
This study was carried out to evaluate the antioxidant, brine shrimp lethality, bioassay and antitumor effects of nhexane, petroleum ether, methanol and chloroform extracts of Annona reticulata leaves. All extracts demonstrated good cupric reducing activity with increasing concentrations keeping methanol extract at the top and n-hexane extract at the second position. The methanol extract was found to have the highest antioxidant capacity 28±26.88 followed by n-hexane 16.95±11.39 and chloroform 12.85±10.32 in the form of mg of ascorbic acid equivalent per gram of crude extract. The methanol extract also showed the highest values of 2.41±0.963 mg of gallic acid equivalent phenolic content and 6.54±4.08 mg of quercetin equivalent flavonoid content per g of crude extract. In the brine shrimp lethality bioassay, LC50 values of methanol, chloroform, petroleum ether, and n-hexane extracts were found to be 1.084?g/ml, 1.096?g/ml, 1.995?g/ml and 3.126 ?g/ml, respectively. These findings suggest that A. reticulata leaves can be a good source of antioxidants and possess significant cytotoxic effect. In a narrow spectrum investigation on antitumor activity of the extracts, we found that the methanol extract inhibited the tumor growing process (control group, chloroform group and petroleum ether group showed significant rise in body weight; i.e., 8% - 14% of initial weight compared to that of methanol group showing a rise of 0.45% - 0.94% of initial weight) and improved ILS (Percentage Increase in Life Span) with increasing doses (Doses of 50mg/kg, 100mg/kg and 200mg/kg showed ILS values of 13.70%, 19.20% and 21.92%, respectively) to some extent when compared with control group and groups receiving other extracts. Bangladesh J Microbiol, Volume 29, Number 2, Dec 2012, pp 70-74